Polymerization - Cankaya, Nevin (IntechOpen, 2018)
The purpose of this book is to help you concentrate on recent developments in polymerization. The chapters collected in the book are contributions by invited researchers with a long-standing experience in different research areas. I hope that the material presented here is understandable to a broad audience, not only chemists but also scientists from various disciplines. The book contains nine chapters in three sections: (1) "General Information about Polymerization," (2) "Biomaterial Content Polymer Composites," and (3) "Mechanical Properties of Polymerization." The book provides detailed and current reviews in these different areas written by experts in their respective fields. This book is expected to be useful for polymer workers and other scientists alike and contribute to the training of current and future researchers, academics, PhD degree students, as well as other scientists.